Técnica de Bobath en el tratamiento fisioterapéutico del retraso psicomotor en niños con síndrome de Down - Lisbeth Jimena, Maya Ruiz (2020)
The investigation focused on the method of bibliographic review, with the main objective being to emphasize the Bobath technique in the physiotherapeutic treatment of psychomotor retardation in children with Down’s Syndrome, as this technique corrects alterations in movement and posture, thus helping to achieve normal movement and stimulating in cases of hypotonia by increasing muscle tone. The application of the Bobath technique and its neurodevelopment therapy is not well known in our workplace, as the lack of scientific articles based on the topic confirms it, despite the little information offered online, it was possible to find 83 scientific articles, by exclusion and valuation on the Pedro scale, a selection of articles was made under these parameters. The number of articles considered suitable for study was 35, as they met a score of 6 or more on the Pedro scale; of these 35 articles, some are in languages such as Portuguese, French, English and Spanish. The present research attempts to emphasize the Bobath technique in the physiotherapeutic treatment of psychomotor retardation in children with Down’s syndrome. The information banks where a large number of scientific articles were found were the following: Scielo, Pubmed, Google Scholar. It was taken as a parameter to consider as suitable an article that meets with a publication date from 2002 to 2019.